Pengaruh Pijat Bayi Terhadap Konstipasi Pada Bayi Usia 1 - 12 Bulan Di PMB A Tahun 2023 - Pratiwi, Lusy; Qomarasari, Desi (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Constipation is a symptom of difficult bowel movements which is characterized by the consistency of hard stools, large size and decreased frequency of bowel movements. Constipation can cause social and psychological problems. Treatment for constipation is to get used to defecating regularly by means of behavior modification, fiber diet, laxatives, and psychological approaches. Massage provides benefits for constipation by stimulating peristalsis and reducing colonic transit time so that it can increase the frequency of bowel movements. The research design uses a pre-experiment, using a static group comparison research design or a comparison with static groups. Results were analyzed using Univariate and Bivariate using the Chy Square test. Based on the results of my research, it can be seen that out of 15 cases of babies who underwent massage therapy, 2 babies (13.3%) had difficult bowel movements, while 13 babies (86.7%) had smooth bowel movements. According to the researcher's assumption, there is no gap between the results of this study and the theory. Baby massage therapy greatly affects the smooth process of defecation. By doing baby massage techniques can facilitate bowel movements.